Tunable light beam steering device using polymer stabilized blue phase liquid crystals - Joshi, Pankaj; Willekens, Oliver; Shang, Xiaobing; De Smet, Jelle; Cuypers, Dieter; Van Steenberge, Geert; Beeckman, Jeroen; Neyts, Kristiaan; De Smet, Herbert (Photonics Letters of Poland, 2017)
A polarization independent and fast electrically switchable beam steering device is presented, based on a surface relief grating combined with polymer stabilized blue phase liquid crystals. Switching on and off times are both less than 2 milliseconds. The prospects of further improvements are discussed. Full Text: PDF References D.C. Wright, et al., "Crystalline liquids: the blue phases", Rev. Mod. Phys. 61, 385 (1989). CrossRef H. Kikuchi, et al., "Polymer-stabilized liquid crystal blue phases", Nat. Mater. 1, 64 (2002). CrossRef Samsung, Korea, SID exhibition, (2008). J. Yan, et al., "Direct measurement of electric-field-induced birefringence in a polymer-stabilized blue-phase liquid crystal composite", Opt. Express 18, 11450 (2010). CrossRef L. Rao, et al., "A large Kerr constant polymer-stabilized blue phase liquid crystal", Appl. Phys. Lett. 98, 081109 (2011). CrossRef Y. Hisakado, et al., "Large Electro-optic Kerr Effect in Polymer-Stabilized Liquid-Crystalline Blue Phases", Adv. Mater. 17, 96 (2005). CrossRef K. M. et al., "Submillisecond Gray-Level Response Time of a Polymer-Stabilized Blue-Phase Liquid Crystal", J. Disp. Technol. 6, 49 (2010). CrossRef Y. Chen, et al., "Level set based topology optimization for optical cloaks", Appl. Phys. Lett. 102, 251106 (2013). CrossRef H. Choi, et al., "Fast electro-optic switching in liquid crystal blue phase II", Appl. Phys. Lett. 98, 131905 (2011). CrossRef Y.H. Chen, et al., "Polarization independent Fabry-Pérot filter based on polymer-stabilized blue phase liquid crystals with fast response time", Opt. Express 19, 25441 (2011). CrossRef Y. Li, et al., "Polarization independent adaptive microlens with a blue-phase liquid crystal", Opt. Express 19, 8045 (2011). CrossRef C.T. Lee, et al., "Design of polarization-insensitive multi-electrode GRIN lens with a blue-phase liquid crystal", Opt. Express 19, 17402 (2011). CrossRef Y.T. Lin, et al., "Mid-infrared absorptance of silicon hyperdoped with chalcogen via fs-laser irradiation", J. Appl. Phys. 113, (2013). CrossRef J.D. Lin, et al., "Spatially tunable photonic bandgap of wide spectral range and lasing emission based on a blue phase wedge cell", Optics Express 22, 29479 (2014). CrossRef W. Cao, et al., "Lasing in a three-dimensional photonic crystal of the liquid crystal blue phase II", Nat. Mat. 1, 111 (2002). CrossRef S.T. Hur, et al., "Liquid-Crystalline Blue Phase Laser with Widely Tunable Wavelength", Adv. Mater. 25, 3002 (2013). CrossRef A. Mazzulla, et al., "Thermal and electrical laser tuning in liquid crystal blue phase I", Soft. Mater. 8, 4882 (2012). CrossRef C.W. Chen, et al., "Random lasing in blue phase liquid crystals", Opt. Express 20, 23978 (2012). CrossRef O. Willekens, et al., "Ferroelectric thin films with liquid crystal for gradient index applications", Opt. Exp. 24, 8088 (2016). CrossRef O. Willekens, et al., "Reflective liquid crystal hybrid beam-steerer", Opt. Exp. 24, 1541 (2016). CrossRef M. Jazbinšek, et al., "Characterization of holographic polymer dispersed liquid crystal transmission gratings", J. Appl. Phys. 90, 3831 (2001). CrossRef C.C. Bowley, et al., "Variable-wavelength switchable Bragg gratings formed in polymer-dispersed liquid crystals", Appl. Phys. Lett. 79, 9 (2001). CrossRef Y.Q. Lu, et al., "Polarization switch using thick holographic polymer-dispersed liquid crystal grating", Appl. Phys. 95, 810 (2004). CrossRef J.J. Butler et al., "Diffraction properties of highly birefringent liquid-crystal composite gratings", Opt. Lett. 25, 420 (2000). CrossRef R.L. Sutherland et al., "Electrically switchable volume gratings in polymer-dispersed liquid crystals", Appl. Phys. Lett. 64, 1074 (1994). CrossRef X. Shang, et al., "Electrically Controllable Liquid Crystal Component for Efficient Light Steering", IEEE Photo. J. 7, 1 (2015). CrossRef J. Yan, et al., "Extended Kerr effect of polymer-stabilized blue-phase liquid crystals", Appl. Phys. Lett. 96, 071105 (2010). CrossRef H.S. Chen, et al., "Hysteresis-free polymer-stabilized blue phase liquid crystals using thermal recycles", Opt. Mat. Exp. 2, 1149 (2012). CrossRef J. Yan. et al., "Dual-period tunable phase grating using polymer stabilized blue phase liquid crystal", Opt. Lett. 40, 4520 (2015). CrossRef H.S. Chen, et al., "Hysteresis-free polymer-stabilized blue phase liquid crystals using thermal recycles", Opt. Mat. Exp. 2, 1149 (2012). CrossRef H.C. Cheng, et al., "Blue-Phase Liquid Crystal Displays With Vertical Field Switching", J. Disp. Technol. 8, 98 (2012). CrossRef